(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2007)
The mathematical model of homogeneous crystallization process, uniting embryos formation and growth of crystals in the conditions of different ranges solution supersaturation on the crystallized matter, is built. Its adequacy is tested on the example of calcium sulphate dihydrate homogeneous crystallization.